1986
DOI: 10.1042/bj2350225
|View full text |Cite
|
Sign up to set email alerts
|

The disaccharides formed by deaminative cleavage of N-deacetylated glycosaminoglycans

Abstract: Chondroitin 4-sulphate, chondroitin 6-sulphate, dermatan sulphate and keratan sulphate were N-deacetylated by treatment with hydrazine and then cleaved with HNO2 at pH 4.0, and the resulting products were reduced with NaB3H4. This reaction sequence cleaved the glycosaminoglycans at their N-acetyl-D-glucosamine or N-acetyl-D-galactosamine residues, which were converted into 3H-labelled 2,5-anhydro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
(24 reference statements)
3
22
0
Order By: Relevance
“…5, human costal cartilage did not serve as an acceptor for the sulfotransferase, while corneal keratan sulfate served as an efficient acceptor. Furthermore, keratanase degradation of 35 S-labeled bovine corneal keratan sulfate did not yield any disaccharide products, consistent with the previous report (19), indicating that the enzyme had no activity on any sulfated internal residue. It has previously been established that human costal cartilage keratan sulfate is essentially 100% Gal 6-sulfated (20), while 50% of the Gal residues of bovine corneal keratan sulfate are unsulfated (35), and it has also been established that Pseudomonas keratanase has no activity on internal residues where the Gal is 6-sulfated (36).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…5, human costal cartilage did not serve as an acceptor for the sulfotransferase, while corneal keratan sulfate served as an efficient acceptor. Furthermore, keratanase degradation of 35 S-labeled bovine corneal keratan sulfate did not yield any disaccharide products, consistent with the previous report (19), indicating that the enzyme had no activity on any sulfated internal residue. It has previously been established that human costal cartilage keratan sulfate is essentially 100% Gal 6-sulfated (20), while 50% of the Gal residues of bovine corneal keratan sulfate are unsulfated (35), and it has also been established that Pseudomonas keratanase has no activity on internal residues where the Gal is 6-sulfated (36).…”
Section: Resultssupporting
confidence: 92%
“…Photoaffinity Radiolabeling-Although PAP 35 S has been shown to be a good photoaffinity label for phenol sulfotransferases (31), our attempts to use this ligand for photoaffinity labeling of the chondroitin 6-sulfotransferase/keratan sulfotransferase were unsuccessful. However, we found that an analog of 3Ј,5Ј-ADP, worked well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligosaccharides were isolated by partial cleavage with hydrazine/hydrazine sulfate treatment (90 min at 100°C), high pH nitrous acid treatment, and NaBH 4 reduction. (Maimone and Tollefsen, 1990;Shaklee and Conrad, 1984). Tritium-labeled CSE oligosaccharides were also obtained by employing [ 3 H]NaBH 4 (Parthasarathy et al, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…At present, the mechanism by which N-glycan attached to the N-5 glycosylation site could stimulate KSST activity is not clear. It has been shown that, in the corneal KS used for the substrate, almost all GlcNAc residues and about a half of the Gal residues are sulfated at position 6 (38). Because C6ST-1 transfers sulfate to position 6 of the Gal residue of KS, the corneal KS contains structures acting as both the substrate and the reaction product of C6ST-1.…”
Section: Discussionmentioning
confidence: 99%